2013
DOI: 10.1007/s10103-013-1421-3
|View full text |Cite
|
Sign up to set email alerts
|

Morphological alterations on Citrobacter freundii bacteria induced by erythrosine dye and laser light

Abstract: The effect of the laser irradiation (532 nm) on films prepared from Citrobacter freundii mixed with erythrosine dye was investigated by using atomic force microscopy. It was observed that morphological changes of bacterial surfaces after irradiations, which were attributed to cellular damage of the outer membranes, are a result of a photodynamic effect. The results suggested that the combination of erythrosine and laser light at 532 nm could be a candidate to a photodynamic therapy against C. freundii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…It was demonstrated that the PS absorption spectrum increases proportionally with its concentration and differs between the two dyes. This results is in accordance with previous studies [ 12 , 22 ] and highlight the importance of taking into account the type of PS in light dose calculations, which are frequently neglected in most of the studies evaluating aPDI effectiveness [ 23 , 24 , 25 ]. A reasonable explation for this finding is provided by the equations demonstrated in the Supplementary Material , where the light dose absorbed (D Abs ) by each photosensitizer is obtained by relating the illumination time ( t ), the irradiated area (A) and the absorbed power (P Abs ) Equation (S11).…”
Section: Discussionsupporting
confidence: 92%
“…It was demonstrated that the PS absorption spectrum increases proportionally with its concentration and differs between the two dyes. This results is in accordance with previous studies [ 12 , 22 ] and highlight the importance of taking into account the type of PS in light dose calculations, which are frequently neglected in most of the studies evaluating aPDI effectiveness [ 23 , 24 , 25 ]. A reasonable explation for this finding is provided by the equations demonstrated in the Supplementary Material , where the light dose absorbed (D Abs ) by each photosensitizer is obtained by relating the illumination time ( t ), the irradiated area (A) and the absorbed power (P Abs ) Equation (S11).…”
Section: Discussionsupporting
confidence: 92%
“…Those authors concluded that erythrosine at 22 µM in the presence of a blue light and infrared diode laser could be considered as a potential approach of PDI against Gram-negative periodontal pathogenic species. Nagata et al [36], in a review of PDI for dental caries, reported that erythrosine is the most hydrophilic photosensitizer and the Gram-positive bacteria allow better penetration of this dye, but Habiboallah et al [35] and Silva et al [37] showed good results with Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…It can be clearly observed that the surface of the membrane tested was completely covered by deposit in which the Citrobacter freundii cells can be seen. As it has been described in [81] they are rod shaped and typically range from 1 to 5 µm in length.…”
Section: Filtration Of Fermentation Broths With Citrobacer Freundii Bacteriamentioning
confidence: 95%